Análisis de la eficiencia en el mercado de eurobonos antes y durante la crisis económica (2004-2012) - José Manuel Guaita Martínez; Maria Luisa Martí Selva; Rosa María Puertas Medina (Journal of Innovation & Knowledge (JIK), 2016)
The aim of this paper is to evaluate the efficiency, using data envelopment analysis, in eurobond issues fixed rate in the period 2004-2012, assessing the impact of the financial crisis in that market. Following the development of a database consisting of 1,999 Eurobonds, the results show that in the years before the crisis starts the efficient issues volume was bigger, being the inefficient ones very close to the border. From 2007, we can see a drastic change in the market conditions, detecting a departure substantial and widespread production frontier.
Keywords: G14; G15; 650; Eurobonds; Efficiency; Economic crisis and spread